C(sp3)–H Peroxidation of 3-Substituted Indolin-2-ones under Metal-Free Conditions - Ying, Wei-Wei; Zhu, Wen-Ming; Gao, Zhanghua; Liang, Hongze; Wei, Wen-Ting (Synlett, 2018)
A C(sp3)–H peroxidation of 3-substituted indolin-2-ones through radical coupling reaction has been developed under metal-free conditions. Using tert-butyl hydroperoxide both as an oxidant and as a peroxidation reagent to couple with the C(sp3)–H bonds of 3-substituted indolin-2-ones can form a new C–O bond without using any additives. This simple strategy provides a green and efficient approach to 3-peroxyindolin-2-ones in moderate to excellent yields. The resulting 3-peroxyindolin-2-ones could be further transformed into 3-hydroxyindolin-2-ones.
Keywords: C(sp3)–H peroxidation; metal-free; 3-substituted indolin-2-ones; tert-butyl hydroperoxide